An investigation of fatigue phenomenon in the upper limb muscle due to short duration pulses in an FES system - Naeem, Jannatul; Azman, Amelia Wong; Khan, Sheroz; Mohd Mustafah, Yasir (IOP Publishing, 2013)
Functional Electrical Stimulation (FES) is a method of artificially stimulating muscles or nerves in order to result in contraction or relaxation of muscles. Many studies have shown that FES system has helped patients to live a better lives especially those who are suffering from physical mobility. Unfortunately, one of the main limitations of an FES system besides of its high cost is largely due to muscle fatigue. Muscle fatigue will affect the training duration which could delay patients' recovery rate. In this paper, we analyzed the occurrence of this fatigue phenomenon in terms of stimulator parameters such as amplitude, frequency, pulse width and pulse shape. The objective of this investigation is to identify other key features of the FES system parameters in order to prolong the training duration among patients. The experiment has been done on a healthy person for the duration of one minute and later the muscles response will be observed. Resultant muscle response is recorded as force using force resistive sensor. The experimental results show muscles will get fatigue at a different rate as the frequency increases. The experiment also shows that the duty cycle is reciprocal to the resultant force.